The Influence of the Discovery Learning Model on Student Learning Outcomes in Class VIII Pressure Material at SMP Negeri 1 Sawit Seberang - Lestari, Bunga Widya (Jurnal Pelita Pendidikan, 2024)
This research aims to determine the effect of the Discovery Learning model on student learning outcomes in class VIII pressure material. ThisThis research aims to determine the effect of the Discovery Learning model on student learning outcomes in class VIII pressure material. This research uses Quasy Experimental Design with a Pretest-Posttest Control design with probability sampling techniques. Data collection was carried out using a multiple choice test with a total of 25 questions. This research involved class VIII students at SMP Negeri 1 Sawit Seberang. Data processing in this study used the SPSS version 25 application. The normality test results showed that the data came from a normal distribution. The homogeneity test shows that the data is homogeneous. In the PairdSample T-Test, the Sig value was obtained. (2-tailed) = 0.000 which indicates a significance value < 0.05 so that Ho is rejected and Ha is accepted. Thus, it can be concluded that the Discovery Learning model has a significant effect on the learning outcomes of Class VIII students on pressure material at SMP Negeri 1 Sawit Seberang.